The multiple faces of extracellular vesicles released by microglia: Where are we 10 years after? - Gabrielli, Martina; Raffaele, Stefano; Fumagalli, Marta; Verderio, Claudia (Frontiers in Cellular Neuroscience, 2022)
As resident component of the innate immunity in the central nervous system (CNS), microglia are key players in pathology. However, they also exert fundamental roles in brain development and homeostasis maintenance. They are extremely sensitive and plastic, as they assiduously monitor the environment, adapting their function in response to stimuli. On consequence, microglia may be defined a heterogeneous community of cells in a dynamic equilibrium. Extracellular vesicles (EVs) released by microglia mirror the dynamic nature of their donor cells, exerting important and versatile functions in the CNS as unbounded conveyors of bioactive signals. In this review, we summarize the current knowledge on EVs released by microglia, enlightening their heterogeneous properties and multifaceted effects.